O METODOLOGIJI PEDAGOŠKEGA RAZISKOVANJA IN KAKO JO POUČEVATI (Филологические заметки, 2019)
The quantity as well as difficulty of methodological contents in curricula must always be submitted to main study discipline. Despite that, one should not neglect the area of methodology since three of five expected graduate learning outcomes described in «Framework for Qualifications of the European Higher Education Area» are (partially or entirely) connected to methodological contents. The purpose of present paper is to outline guidelines for devising methodology-related parts of study programs for educational professions. Proposed guidelines are based on following three premises: - Specifics of educational research (as well as research in education) compared with other social sciences. - Epistemological and ethical consideration including (post)modern theoretical streams such as constructivism in education, participatory position, grounded theories, transition from general «valid-for-all» procedures to so called examples of good praxis. - Sketch of current student’s attitude towards methodology. Guidelines, following from above-mentioned theoretical concepts and observations are divided into two parts. 1. General recommendations, related to expected study outcomes and competences: awareness of context, education for methodical work, practice of the skill of concise reporting of observations, research etc. 2. Concrete propositions for curricula development. In this section, paper concentrates on selected specific methodological topics such as importance of understanding basic statistical toolbox, action research and case study, observation, skill of assessment of concrete educational situation and observer’s (researcher’s) role in it.